2005
DOI: 10.3122/jabfm.18.2.125
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the Diagnosis and Treatment of Depression in Jordan. A Nationwide Qualitative Study

Abstract: Background: Depression is one of the most common causes of morbidity in developing countries. It is believed that there are many barriers to diagnosis and treatment in the primary care setting, but little research exists.Methods: Five focus groups were conducted with the goal of exploring themes related to barriers to the diagnosis and treatment of depression, with a purposeful nationwide sample of 50 primary health care providers working in the public health clinics of the Jordanian Ministry of Health (MOH). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 9 publications
1
47
0
Order By: Relevance
“…It is also not clear whether depression leads to smoking or smoking leads to depression. Existing data indicate that lack of patient acceptance of the diagnosis of depression is one of the major barriers to identification and treatment of depression in Jordanians [68] . This is an area that requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also not clear whether depression leads to smoking or smoking leads to depression. Existing data indicate that lack of patient acceptance of the diagnosis of depression is one of the major barriers to identification and treatment of depression in Jordanians [68] . This is an area that requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Education is needed for health care providers, particularly physicians, about identification, diagnosis and treatment of major depression. Providing referral of patients with major depression to specialized medical care (counseling and pharmacological treatment) is recommended to treat depressed patients [68] .…”
Section: Discussionmentioning
confidence: 99%
“…One study from Zimbabwe suggested that over 90% of primary health care workers acknowledged deficiencies in the recognition and knowledge of treatment for depression (43). Lack of knowledge among health care professionals may be compounded by the stigmatization of mental illness, with some studies indicating that many professionals believe that such conditions either do not exist or cannot be treated (44). Stigmatization might also mean that only physical symptoms or comorbid conditions are treated, rather than the underlying disease.…”
Section: Diagnosis Of Disordersmentioning
confidence: 99%
“…The survey conducted in United Arab Emirates revealed that the depression rate in the life-time for females is 9.5%; whereas, for males is 2.5%. The survey also found that the depression rate is higher in women; accordingly, the ratio of depression among both females and males is 4:1 (3,4).…”
Section: Introductionmentioning
confidence: 83%
“…The reason behind the depression in adolescents of Jordan is differences in the socio-cultural settings, inappropriate management settings of medical, and lack of resources. Moreover, Jordan adolescents are highly dependent on their parents; due to which, they experience abnormal psychological and social reactions during their personal and professional life (3,4).…”
Section: Introductionmentioning
confidence: 99%